2009
DOI: 10.1007/s10265-009-0233-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of carbon balance in the reproductive organs and leaves of Cinnamomum camphora (L.) Presl

Abstract: We investigated seasonal changes in dry mass and CO(2) exchange rate in fruit and leaves of the evergreen tree Cinnamomum camphora with the aim of quantitatively determining the translocation balance between the two organs. The fruit dry mass growth peaked in both August and October: the first increase was due to fruit pulp development and the second to seed development. Fruit respiration also increased with the rapid increase in fruit dry mass. Therefore, the carbohydrates required for fruit development showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…The fruits of some evergreen tree species have photosynthetic activity, although their contribution is generally low (Ogawa et al . , Imai & Ogawa ). Dipterocarp fruit wings have low photosynthetic ability (Kenzo et al .…”
Section: Amount Of Reproductive Organs Number Of Days With 30‐day Momentioning
confidence: 94%
“…The fruits of some evergreen tree species have photosynthetic activity, although their contribution is generally low (Ogawa et al . , Imai & Ogawa ). Dipterocarp fruit wings have low photosynthetic ability (Kenzo et al .…”
Section: Amount Of Reproductive Organs Number Of Days With 30‐day Momentioning
confidence: 94%
“…The dry mass/fresh mass ratio of fruits can be used to assess the different phases of fruit growth (Imai and Ogawa 2009). In present study, fruit development of hickory can be divided into two phases according to the fruit growth pattern.…”
Section: Fruit Developmentmentioning
confidence: 99%
“…Fruit respiration can be separated into two components: maintenance respiration, which supplies the energy necessary for maintaining a healthy existing phytomass and growth respiration, which is required for the synthesis of new phytomass (Amthor 1989(Amthor , 2000. Imai and Ogawa (2009) suggested that increased dark respiration on a fruit basis is related to the fast dry mass accumulation for the fruit and seed development. Thus, we suggest that the increase of R d on a fruit basis is due to the growth respiration by fruit and seed development.…”
Section: Fruit Developmentmentioning
confidence: 99%
See 2 more Smart Citations